Interactions Between the Aging Gut Microbiome and Common Geriatric Giants: Polypharmacy, Frailty, and Dementia. (17th February 2020) - Gemikonakli, Gizem; Mach, John; Hilmer, Sarah Nicole
Abstract: The gut microbiome has pervasive bidirectional relationships with pharmacotherapy, chronic disease, and physical and cognitive function. We conducted a narrative review of the current literature to examine the relationships between the gut microbiome, medication use, sarcopenia and frailty, and cognitive impairment. Data from in vitro experiments, in vivo experiments in invertebrates and complex organisms, and humans indicate associations between the gut microbiome and geriatric syndromes. Better understanding of the direct and indirect roles of the microbiome may inform future prevention and management of geriatric syndromes.